Epidemic typhus and other louse- and mite-borne infections - Macaluso, Kevin (Henry Stewart Talks, 2010)
Louse characteristics including biology, taxonomy and species of medical importance, Louse-borne infections, Ecology and epidemiology of epidemic typhus, trench fever and relapsing fever, Mite characteristics including biology, taxonomy, and species of medical importance, Mite-borne infections, Ecology and epidemiology of rickettsialpox and scrub typhus